1984
DOI: 10.1147/rd.286.0697
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure evolution during electroless copper deposition

Abstract: A study using transmission and scanning electron microscopy was made of the evolution of the microstructure of electroless plated Cu on activated amorphous substrates and on singlecrystal Cu grains. On amorphous substrates activated in a PdClj-SnClj colloidal solution, Sn atoms dissolved into the plating solution concurrently with Cu deposition on the substrate during the initial stage of deposition. The very small face-centered-cubic grains of Cu-Pd solid solution agglomerated into much larger particles and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 15 publications
4
31
0
Order By: Relevance
“…Redistribution subject to ECS terms of use (see 169.230.243.252 Downloaded on 2014-11-19 to IP the rocking curve scans collected from CVD Ru, indicating the random orientation. Similar substrate related growth behavior of both electrolytic copper and electroless copper were reported previously (3)(4)(5)(6). …”
Section: Resultssupporting
confidence: 85%
“…Redistribution subject to ECS terms of use (see 169.230.243.252 Downloaded on 2014-11-19 to IP the rocking curve scans collected from CVD Ru, indicating the random orientation. Similar substrate related growth behavior of both electrolytic copper and electroless copper were reported previously (3)(4)(5)(6). …”
Section: Resultssupporting
confidence: 85%
“…It was reported that the surface energy of copper surface (100) is 2910 erg/cm 2 while the surface energy of copper surface (111) is 2530 erg/cm 2 [13]. Previous studies have demonstrated that face centered cubic materials often have a b111N preferred orientation because the (111) planes have a relatively low surface energy, and the low-surface-energy (111) copper planes are frequently observed on electrodeposited copper surfaces [14]. As a result, we can conclude that the habit formation of the crystal should be the formation mechanism of those equilateral triangles.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with initial deposition occurring as the adsorbed intermediate AuCN, as postulated for electrodeposition of Au onto a variety of metal substrates. [44][45][46][47][48] The reduction of Au(CN) 2 Ϫ has been proposed to occur by two parallel processes, direct reduction by reaction 1 at high overpotentials and a two-step reduction process at low potentials [44][45][46][47][48] Au(CN) 2 Ϫ r AuCN(ads) ϩ CN Ϫ [5] AuCN(ads) ϩ e Ϫ r Au ϩ CN Ϫ [6] Surprisingly, SERS has only identified adsorbed Au(CN) 2 Ϫ , 49,50 although evidence for incorporation of nanocrystalline AuCN into Au deposits has been obtained by transmission electron microscopy (TEM) and Auger electron spectroscopy (AES). 51 An alternative explanation to the two-step reduction process described would be initial deposition into a partially discharged species, followed by full reduction and incorporation into a Au nanocluster.…”
Section: Resultsmentioning
confidence: 99%